Core mechanism and therapeutic methods of aging revealed by Qi-collateral theory in traditional Chinese medicine - Hongrong Li; Yunlong Hou; Xuan Lu; Lu Wang; Mengnan Li; Ning Kang; Yiling Wu (Science of Traditional Chinese Medicine)
Abstract. Aging, a complex and multisystem process, has increasingly become a hot issue of global concern. Traditional Chinese medicine has accumulated rich understanding of aging during thousands of years of development, which provides valuable references for the in-depth study of overall aging. According to the Qi-collateral theory in traditional Chinese medicine, essence is the origin of life; Qi is the driving force of life; and spirit is the embodiment of life. This theory interprets key scientific issues such as the formation of life, the driving force of life, the function of Zang-Fu organs, and the spirit and consciousness. Furthermore, it reveals the key mechanism of aging. That is, the deficiency of kidney essence is the root of aging; the loss of vitality is the key of aging; and the depletion of body and spirit is the manifestation of aging. Based on the experience of medical practitioners in the past dynasties, such as nourishing essence, black food tonifying the kidney, and supplementing essence with flesh-blood products, the treatment method of invigorating kidney and supplementing essence, harmonizing Yin and Yang, reinforcing the vitality, and nourishing the body and spirit was proposed. Furthermore, an innovative Chinese patent medicine, Bazi Bushen capsules, is developed, which exerts the antiaging effect by replenishing Qi, invigorating the spirit, and nourishing the body and spirit. Pharmacological and clinical studies have confirmed that this preparation has antiaging effects and are effective in the prevention and treatment of age-related diseases. Experimental studies have shown that Bazi Bushen capsules can delay the overall aging, reduce the DNA methylation and extend the healthy life of naturally aging mice, mitigate the age-related cognitive dysfunction, improve neurological function, maintain redox homeostasis and telomere integrity, and inhibit apoptosis. Moreover, Bazi Bushen capsules can increase the dermal thickness and the collagen fiber and elastic fiber content to prevent skin aging. In addition, Bazi Bushen capsules can correct the lipid metabolism disorders and ameliorate multisystem age-related diseases such as osteoporosis in surgically induced menopausal rats. This article discusses the pathogenesis, treatment, and prescription of aging and the antiaging theory, aiming to provide a basis for delaying aging and preventing related diseases.